SOCIALIST PAST IN THE MODERN "POLITICAL" MEMORY OF SLOVAKIA: ANALYSIS OF THE OFFICIAL INTERPRETATION TOOLS - L. P. Nelina; N. E. Demeshko (Современная наука и инновации, 2022)
This article is an intermediate result of the study of contemporary instruments of memory policy in the Slovak Republic. Taking the concept of "political" memory as a starting point, the authors reveal the main technologies of its formation used by modern Slovak authorities. The research is based on Slovak laws regulating the interpretation of events in national history and the annual reports on the activities of National Memory Institute in Bratislava for the years 2003-2019. The study found that the conceptual basis of memory policy in this country remains the concept of totalitarianism, developed during the Cold War, elevated to the level of political doctrine, asserting the identity of all socialist regimes with fascism as a historically discredited ideology and system. In 2002, this identity was enshrined in law, introducing the definition of the "period of non-freedom" 1939-1989. The authors conclude that the purposeful discrediting of the socialist past essentially serves as an additional tool for the internal legitimization of the democratic present, the relevance of the use of which seems to persist.